Developing Practical Skills in Differentiated Learning: Training for Prospective Teachers in Malaysia - Bagus Cahyanto; Fita Mustafida; Hafiz Udabi Ersyan Syahputra (Universitas Nurul Jadid, 2024)
This training was conducted for prospective teachers at Universiti Kebangsaan Malaysia (UKM) to develop participants' understanding and practical skills in differentiated learning. This community service was designed in several stages including preparation, socialization, mentoring, and monitoring and evaluation of activities. The training materials included materials on student diversity, dimensions of diversity, equality and justice in learning, learning according to ability level, basic principles of differentiated learning, strategies for differentiating learning, and assessment in differentiated learning. The community service team also provided assistance to participants in preparing learning designs and ended with filling out a questionnaire to assess the implementation of the training as a whole. The results of the questionnaire showed that 93% of participants experienced an increase in understanding, 95% were motivated to implement differentiated learning and 100% of participants gave a positive response to the community service activities.